Quality of curly kale cultivated under hydroponic system using biofertilizer by leaf fertilization - Pereira, José Maurício (2021)
This study aimed to evaluate the agronomic, physicochemical and sensory characteristics of curly kale cultivated under hydroponic system, with and without leaf fertilization. For the agronomic analysis, the following parameters were evaluated: the lengths of the stem, leaf, petiole, whole plant and root system; stem diameter, leaf width; fresh mass of the stem, leaf, whole plant and root system, and number of leaves per plant. The physicochemical analyses evaluated were: moisture of the leaves and root, soluble solids, pH, chlorophyll index and instrumental color. For the sensory analysis, the triangle test was applied to verify a possible difference between the treatments, with tabulated interpretation. An acceptance test was applied. The data from the agronomic and physicochemical analyses, acceptance and purchase intention were evaluated by analysis of variance and Tukey’s test (p≤0.05). The treatments did not differ statistically regarding either the agronomic parameters or chlorophyll, soluble solids, and pH. The analysis of instrumental color demonstrated that the kales with leaf fertilization presented lower luminosity and lower green color intensity. The evaluators noticed a difference between the treatments. However, there were no differences in the acceptance of the sensory attributes evaluated nor in purchase intention.   Keywords: Brassica oleracea L. var. acephala. Color. Hydroponics. Fertilization. Acceptance.